Exploring the Well-Being of Guidance Counselors in the Philippines: A Phenomenological Study - Maria Theresa B. Gallardo; Maria Lourdes L. Chavez (Philippine Social Science Journal, 2022)
Guidance Counselors are professionals with a specialized practice that ensures the holistic development of students. Despite their crucial role, there is little research exploring the experiences and perceptions of guidance counselors in terms of wellness programs, well-being, self-care practices, and retention. This study aims to create research and evidence-based interventions to improve well-being and maintain work satisfaction among guidance counselors. Using Giorgi’s phenomenological qualitative approach, this study is based on interviews conducted with twelve (12) guidance counselors from Luzon, Visayas, and Mindanao. The findings suggest improving wellness programs, namely, physical, mental, and spiritual programs, a strong support system among colleagues, and other incentives and forms of compensation. It was also found that a healthy work environment is a key to FGC retention, which consists of harmonious work relationships, a strong support system, psychological safety, counselor training, further education, and a flexible and accommodating workload and schedule. Financial elements also come to play and other long-term benefits of employment. Intrapersonal factors include self-care and personal commitment. The current research recommends utilizing the proposed wellness and retention program framework and offered mental health and wellness programs of FGC.